La formation de paysagiste au Chili de 1960 à nos jours. Émergences et évolutions comparatives de deux cursus universitaires de premier cycle - Claudia Márquez Thomas (Projets de Paysage)
Little research has been conducted on the history of academic training in landscape architecture in Chile. In this article we define two key periods by analysing the contexts of the emergence and development of two university undergraduate courses : those of the Universidad de Chile between 1960 and 1980 and of the Universidad Central since 1988. Our research is based on interviews with key actors of these two periods and the review of pedagogical publications. During these six decades, the training of landscape architects evolved from applied landscape design associated with interior decoration and the design of green spaces such as gardens to large urban parks to finally address the domain of large urban, rural and natural landscapes, referred to under the term of landscape architecture. As the scale of interventions increased, the gardening and garden design aspects tended to disappear. Nevertheless, the review of these two training programmes makes it possible to look back on the development of a discipline which often remains misunderstood and has constantly redefined itself to adapt to social issues.